2002
DOI: 10.1259/bjr.75.897.750748
|View full text |Cite
|
Sign up to set email alerts
|

Does cardiologist- or radiographer-operated fluoroscopy and image acquisition influence optimization of patient radiation exposure during routine coronary angiography?

Abstract: The operator of radiation exposure during coronary angiography varies between different centres. The purpose of this study was to explore whether radiation dose was lower during cardiologist- or radiographer-controlled radiation exposure and to determine if the grade of cardiologist performing angiography influenced radiation dose. Patients were randomly allocated either to cardiologist- or radiographer-controlled radiation exposure during coronary angiography. Screening time and radiation dose during fluorosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Furthermore, there may have been variations in the training of the senior cardiologists, whereas at other centres, radiation exposure may or may not be under their control. Arthur et al [30] proposed that, without adequate training to control radiation exposure, cardiologists in training may progress to the consultant stage and bypass the learning curve necessary to reduce radiation doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there may have been variations in the training of the senior cardiologists, whereas at other centres, radiation exposure may or may not be under their control. Arthur et al [30] proposed that, without adequate training to control radiation exposure, cardiologists in training may progress to the consultant stage and bypass the learning curve necessary to reduce radiation doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no published data on whether the radiation dose with biplane or single-plane imaging during coronary angioplasty differs between the three vascular territories: right coronary artery (RCA), left anterior descending (LAD) and left circumflex/intermediate (LCX). Furthermore, interventional cardiac procedures are operator dependent [28][29][30]. Hence, it was postulated that senior cardiologists would be more familiar with biplane equipment and thereby more able to reduce radiation dose, contrast load and procedural time than less experienced operators.…”
mentioning
confidence: 99%
“…Bernardi et al [57] and Padovani et al [60] investigated the effect of the complexity of PCI procedures on patient exposure by dividing the procedures in ‘simple’, ‘medium’ and ‘complex’ based on a set of indexes and they found correlation between patient dose and procedural complexity. Arthur et al [31] explored whether radiation dose was lower during cardiologist- or radiographer-controlled radiation exposure and determined whether the grade of the cardiologist influences radiation dose. They found that cardiologist-operated exposure and senior cardiologists result in lower radiation doses during CA.…”
Section: Discussionmentioning
confidence: 99%
“…The restricted number of studies on dynamic FP detectors found in the literature, 6–9 the fact that PCI is a convoluted, delicate, and lengthy procedure associated with increased radiation dose 10–13 , and that the only clinical study in FP imaging in IC was a preliminary work reported by the authors 8 induced us to investigate this procedure in more detail. As part of the European DIMOND research project, 14 a local patient survey was performed using a common protocol for patient collection agreed among the DIMOND partners so as to explore the clinical and technical factors that have an impact to the amount of radiation dose imparted to the patient during PCI, based on the work of Bernardi et al 3 and Padovani et al, 15 and check whether FP digital technology actually facilitates the reduction of radiation dose when compared to conventional II equipment with cine film recording which is still used in many centers across the world.…”
Section: Introductionmentioning
confidence: 99%